Effect of montelukast on remission maintenance in patients with ulcerative colitis: a Randomized, double-blind controlled clinical trial - Kourosh Masnadi Shirazi; Mehran Nezam Diba; Arman Masnadi Shirazinezhad; Zeinab Nikniaz (BMC Gastroenterology)
Abstract Background Considering the role of leukotrienes in inflammatory pathways, and owing to the anti-leukotrienes effect of montelukast, in the present clinical trial, we aimed to assess the effect of montelukast on remission maintenance in patients with ulcerative colitis (UC). Methods In the present double-blind randomized controlled clinical trial, 222 volunteer UC patients on high-dose corticosteroid and montelukast were recruited. The patients received 10 mg of montelukast (98 patients) or placebo (124 patients) for 22 weeks. Simultaneously, the prednisolone dose was tapered. The patients were followed up eight more weeks post-interventions. The primary efficacy of the treatment was remaining in remission. Results 194 patients completed this study. During the study, relapse occurred in 108 patients, 32 patients in the montelukast group and 76 patients in the placebo group. There were significant differences between groups regarding the relapse-free period (intervention group mean: 27.25 95% CI: 26.17–28.32 weeks and placebo group mean: 20.88; 95% CI: 19.36, 20.40 weeks, P < 0.001). At the end of the intervention period and six weeks’ post-intervention, the mean partial Mayo score, and inflammatory biomarkers were significantly lower in the montelukast group compared with the placebo group. The frequency of patients with high fecal calprotectin levels was significantly higher in the placebo group compared with the montelukast Group. Conclusion The findings indicated that compared with placebo, montelukast had a significant positive effect on remission maintenance in UC patients who were in the steroid-tapering phase of therapy. Clinical trial registration number IRCT20121212011738N3.